Spring Recipes A Problem-Solution Approach - Mak, Gary. (Apress : Imprint: Apress, 2008)
Spring addresses most aspects of Java/Java EE application development and offers simple solutions to them. By using Spring, you will be lead to use industry best practices to design and implement your applications. The releases of Spring 2.x added many improvements and new features to the 1.x versions. Spring Recipes: A Problem–Solution Approach focuses on Spring 2.5 features for building enterprise Java applications. Spring Recipes covers Spring 2.5 from basic to advanced, including Spring IoC container, Spring AOP and AspectJ, Spring data access support, Spring transaction management, Spring Web and Portlet MVC, Spring testing support, Spring support for remoting, EJB, JMS, JMX, E–mail, scheduling, and scripting languages. This book also introduces several common Spring Portfolio projects that will bring significant value to your application development, including Spring Security, Spring Web Flow, and Spring Web Services. The topics in this book are introduced by complete and real–world code examples that you can follow step by step. Instead of abstract descriptions on complex concepts, you will find live examples in this book. When you start a new project, you can consider copying the code and configuration files from this book, and then modifying them for your needs. This can save you a great deal of work over creating a project from scratch.